Issues of Federalism in Nepal: A Political Analysis of Success Factors - Jero Rai, Ram Kumar (NPRC Journal of Multidisciplinary Research, 2025)
This paper critically examines the evolution, implementation, and challenges of federalism in Nepal, contextualizing it within both theoretical frameworks and global empirical experiences. Drawing on qualitative methods under a critical paradigm, the study employs a systematic review of scholarly literature, legal texts, and institutional reports to analyze Nepal’s federal transition post-2015 Constitution. The paper identifies key structural enablers—such as constitutional clarity, fiscal decentralization, intergovernmental coordination, and local autonomy—and evaluates their operational status in Nepal’s three-tier governance. Comparative insights from the United States, Soviet Union, Nigeria, Yugoslavia, Germany, Ethiopia, and the European Union highlight how institutional strength, ethnic accommodation, and distributive equity shape the success or failure of federal systems. The findings suggest that Nepal’s federalism, while normatively robust, remains constrained by implementation deficits, weak institutional capacity, and political instability. The paper recommends legal harmonization, fiscal equity, participatory governance, and strengthened anti-corruption mechanisms as critical measures for sustaining inclusive federalism in Nepal.